All China federation of trade unions: Structure, functions and the challenge of collective bargaining - Rudolf Traub-Merz (International Labour Organization (ILO), 2011)
In China, the All China Federation of Trade Unions (ACFTU) is the sole legal trade union organisation. It was established in 1925 and over the years and decades has gone through many changes. After 1949 it was restructured according to the needs of a socialist command economy and became the »transmission belt« through which the Party controlled workers. The year 1978 was again a turning point, when China started its liberalisation and, fed by surplus labour from a peasant economy, gradually re-established labour markets. Since then, the system of industrial relations at all levels has been undergoing profound changes, in parallel with which the traditional functions of ACFTU are being challenged. The process of adjusting industrial relations to the return of privately-owned companies is taking place in a situation in which the Communist Party of China (CPC) and ACFTU are maintaining their traditional bonds and ACFTU continues to function as an extension of the party-state. There are many questions about the future of this relationship. In view of intensifying labour protests and strikes for higher wages, ACFTU is facing a dilemma: should it side with the workers or act as a mediating force whenever labour conflicts arise? The relations between the CPC and ACFTU and the functional embedding of Chinese union organisations in industrial relations have a great bearing on the Chinese political economy. This chapter takes ACFTU as the focus of its analysis. After a brief look at its history before 1949 (Section 1) it looks at the transformation of industrial relations under the socialist command economy and analyses the organisational profile of unions and the ways they interact with the party-state (Section 2). Section 3 marks the adaptation of industrial relations to the labour markets which evolved after 1978 around migrant labour and through public sector reform, while Section 4 deals with ACFTU's strategies for organising the private sector. Mediation and lobbying are key functions of ACFTU (Section 5), but growing labour conflicts and, in particular, wage strikes are presenting unions in China with new challenges (Section 6). Finally, Section 7 assesses the extent to which ongoing interventions can serve as successful strategies for building collective bargaining around the official union organisations.
Keywords: 330; trade union federation; unionized worker; collective bargaining; mediation; wages; labour dispute settlement; China